Law Due To The Transfer of Land Deed With Hands Down As Evidence - Eka Devi Febriyanti; Moh. Abd Basith; Widhi Handoko (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The purpose of this study were 1) To explain the legal consequences on the transition of land right under the deed of hand as evidence, 2) To explain the Deed Under Power of Hands For Evidence. This study, using normative juridical research and studied approach to legislation (the statute approach) which means that a problem will be seen from the legal aspect and to examine the legislation, then linked to the issues discussed, with material collected by conduct a literature study. Based on this research can be concluded 1)The legal consequences on the transition of land right under the deed of hand as evidence is not valid, because deed made and prepared by the parties to the contract in person, and not before a notary or other authorized officials.Deed under the hand strength can be absolute proof of the deed if legalized or notarized. Deed under hand notarized the deed generally made by the parties concerned on the agreement of both parties, while on his signature or thumbprint and executed before a notary. 2) Every deed under the hand required spiked with a letter dated statement from a notary or an officer appointed by the Act. Function deed under the hand that was authorized notary is certainty over the signature as that is party to sign it certainly was not anyone else.Keywords: As a result of the Law; Transfer of Rights to Land; Hands Down Deed; Evidence.